Running performance is correlated with creatine kinase levels and muscle soreness during an olympic games in hockey - McMahon, G. E.; Sharp, L. E.; Kennedy, R. A. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To compare the global positioning system- and accelerometry-derived running demands, creatine kinase (CK), and self-reported wellness during an Olympic Games in international hockey.